Effectiveness of multimedia approaches in embryology teaching: a scoping review - Hadie, Siti Nurma Hanim; Dasiman, Razif; Omar, Noorkardiffa Syawalina; Abas, Razif (Universiti Putra Malaysia Press, 2023)
Embryology is a critical subdiscipline in medical education, focusing on human body organ development and providing a foundation for understanding developmental anatomy. However, traditional teaching methods using static 2D graphics in textbooks may hinder students' comprehension of the complex 3D embryonic growth processes. To address this, multimedia approaches, such as animations, videos, and interactive tools, have been explored for effective embryology education. This scoping review identifies five key elements of successful multimedia teaching in embryology: multimodal integrated instructional content, cognitive load-reduction strategies, cognitive engagement and physical interactivity, learner-controlled multimedia instruction, and development of tacit knowledge. These strategies promote active learning, enhance students' understanding, and foster critical thinking skills. Future research should focus on evaluating the impact of multimedia approaches on students' engagement, attitudes, and competency development. Embracing multimedia in embryology education can improve medical students' clinical understanding and support effective medical practice.